Improving Foley Catheter Insertion Procedure by Developing Foley Introducer: A 100-Year Overdue Innovation - Khae Hawn Kim; Kyung Jin Chung (International Neurourology Journal, 2023)
Purpose Foley catheter (FC) insertion is very basic yet one of the most widely performed procedures all across the fields of medicine. Since FC was first introduced in 19020’s, no significant improvement has been made in view of methodology, despite the inconvenience associated with cumbersome preparation, procedure, and the patients’ discomfort with having to have their genitalia exposed. We developed a new, easy-to-use FC insertion device, Quick Foley, that provides an innovative approach to introducing FC while simplifying and minimizing time spent without compromising the sterility. Methods We developed an all-in-one disposable FC introducer contains all the necessary components in a single-device-kit. Minimal plastic components are necessary to keep accuracy and consistency, but the rest are made of the paper to minimize plastic waste. The preparation is done by connecting to the drainage bag, spurring the lubricant gel through gel insert, separating the tract, and connecting with the ballooning syringe. For the insertion, after sterilizing the urethral orifice, rotate the control knob to feed FC to the end of the urethra. After ballooning, dissembling of the device is done only by opening and removing the module, then only the FC remains. Results As the device is all-in-one, there is no need to prearrange the FC tray, simplifies the FC preparation and catheterization procedure. This device not only makes it convenient for the practitioner, but ultimately, it will reduce the psychological discomfort experienced by patient by truncating perineal exposure time. Conclusions We have successfully developed a novel device that reduces the cost and burden of using FC for practitioners while maintaining an aseptic technique. Furthermore, this all-in-one device allows the entire procedure to be completed much more quickly compared to the current method, so this minimizes perineal exposure time. Both practitioners and patients can benefit by this new device.